(untitled) (Ameghiniana, 2013)
PALYNOLOGY OF THE POTRERILLOS AND CACHEUTA FORMATIONS, MENDOZA PROVINCE, ARGENTINA.- Spores and pollen grains are described from the Potrerillos and Cacheuta Formations. The sediments yielded 13 species, 12 of which are assigned to specífíc ranges. Cadargasporítes cuyanensis sp. nov. is descríbed, the genus having been previously reported in the Triassic and Jurassic age of Australia and also in the Argentine Cuyana and Neuquina basins. Pollen grains are more abundant than spores in the Potrerillos Formation while this relation is reversed in the Cacheuta Formation. The difference is attributed to a change in ecofacies, although there is also a short chronological varíation. Since this spore and pollen association has now been recognízed in several basins, the name Cadargasporites assemblage is proposed. The Fossíliferous strata appear to be of Late Triassic age.